2021
DOI: 10.1101/2021.08.17.456698
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Longitudinal monitoring of individual infection progression in Drosophila melanogaster

Abstract: The innate immune system is critical for host survival of infection. Infection models in organisms like Drosophila melanogaster are key for understanding evolution and dynamics of innate immunity. However, current toolsets for fly infection studies are limited in their ability to resolve changes in pathogen load on the hours time-scale, along with stochastic responses to infection in individuals. Here we report a novel bioluminescent imaging strategy enabling non-invasive characterization of pathogen load over… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…We have shown that the SPPL does indeed increase with the initial dose x 0 when it is transient, while it is independent from initial conditions when stable. Those results are in line with empirical results as the SPPL depends on initial inocculum when Drosophila are infected by pathogenic bacteria (Acuña Hidalgo et al, 2021;Chambers et al, 2019;Duneau et al, 2017a), but not when infected by non-pathogenic bacteria such as E. coli (Ramirez-Corona et al, 2021). We therefore propose that testing the link between the SPPL and the initial dose is a way to experimentally demonstrate that the control over infection is transient.…”
Section: Bistability Can Make the Sppl Transientsupporting
confidence: 86%
See 1 more Smart Citation
“…We have shown that the SPPL does indeed increase with the initial dose x 0 when it is transient, while it is independent from initial conditions when stable. Those results are in line with empirical results as the SPPL depends on initial inocculum when Drosophila are infected by pathogenic bacteria (Acuña Hidalgo et al, 2021;Chambers et al, 2019;Duneau et al, 2017a), but not when infected by non-pathogenic bacteria such as E. coli (Ramirez-Corona et al, 2021). We therefore propose that testing the link between the SPPL and the initial dose is a way to experimentally demonstrate that the control over infection is transient.…”
Section: Bistability Can Make the Sppl Transientsupporting
confidence: 86%
“…Our model predicts that stable SPPLs are, conversely, independent from how the infection is initiated. In particular, they are insensitive to inoculum size, in accordance with benign Escherichia coli infections of D. melanogaster (Ramirez-Corona et al, 2021). The stable SPPL therefore reflects stable genetically determined characteristics of both the host and the pathogen, but it is affected by traits related to both tolerance and resistance.…”
Section: Exploring Chronicity: Stable and Unstable Set-point Pathogen Loadsmentioning
confidence: 85%